'Placement budgets' for supported employment: impact on employment rates in a multicentre randomised controlled trial. (June 2020) - Rössler, Wulf; Kawohl, Wolfram; Nordt, Carlos; Haker, Helene; Rüsch, Nicolas; Hengartner, Michael P.
Abstract : Background: The most effective rehabilitation model for job (re-)entry of people with mental illness is supported employment. A barrier to introducing supported employment into standard care is its temporally unlimited provision, which conflicts with health and social legislation in many European countries. Aims: To test the impact of different 'placement budgets', i.e. a predefined maximum time budget for job seeking until take-up of competitive employment. Method: Participants (116) were randomly assigned to 25 h, 40 h or 55 h placement budgets in an intent-to-treat analysis. We applied the individual placement and support model over 24 months, following participants for 36 months. Primary outcome was employment in the labour market for at least 3 months. Results: The proportion of participants obtaining competitive employment was 55.1% in the 25 h group, 37.8% in the 40 h group and 35.8% in the 55 h group. In a Cox regression analysis, time to employment was slightly lower in the 25 h group relative to the 40 h (hazard ratio 1.78, 95% CI 0.88–3.57, P = 0.107) and 55 h groups (hazard ratio 1.74, 95% CI 0.86–3.49, P = 0.122), but this was not statistically significant. The vast majority of all participants who found a job did so within the first 12 months (80.4%). Conclusion: A restricted time budget for job finding and placement does not affect the rate of successful employment. In accordance with legislation, a restriction of care provision seems justified and enhances the chances of supported employment being introduced in statutory services.